Socio-Cultural Factors on the Tradition of Consuming Sweet Food Dishes during Events in Central Java with the Incidence of Diabetes Mellitus - Fitri Nur Fadhillah (Syntax Idea)
The high number of diabetes mellitus sufferers in Indonesia is a serious concern because of the very high risk of other diseases and even death. One aspect that needs to be considered is the behavior of consuming sweet foods which is still an inseparable part of Central Javanese cultural traditions. This research aims to analyze socio-cultural factors regarding the tradition of consuming sweet dishes during the Tedhak siten event in Central Java with the incidence of diabetes mellitus. This research uses a literature review research method with library study data collection techniques. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that socio-cultural factors, such as the tradition of sweet foods at events in Central Java, have a complex relationship with the incidence of diabetes mellitus. Even though this tradition has important cultural values in Central Javanese society, consuming sweet foods excessively or too often can increase the risk of developing diabetes mellitus. So it is important for people to pay attention to their food choices in order to avoid and reduce the high risk of developing diabetes mellitus, even though this tradition has strong cultural values